Multiple voices and multiple interests: students’ lived experiences and understanding of university internationalization - Sung, Min-Chuan; Wang, Yan; Vong, Keang Ieng Peggy (Asia Pacific education review, 2025)
With internationalization of higher education (HE) a worldwide trend in the past decades, a bulk of research has investigated various related issues, yet students’ voices have been largely absent from the current discussion of university internationalization. This study explored Chinese students’ constructive understandings of internationalization based on their actual experiences in one university of Greater China. Applying Habermas’s framework of knowledge-constitutive human interests to the focus-group interview data, the study uncovered students’ diversified voices, expressing views of internationalization as their “future business card(s)” and as cross-cultural learning experiences. Other views were represented by the metaphor of “neritic fish,” used to describe a university who lost its identity in pursuing internationalization, and by criticism of their own institution on “being internationalized” in the current wave of global HE internationalization, rather than, “internationalizing”, with suggestions of building a university’s internal strengths as the pre-condition for genuine internationalization. While some of these views showed congruence with the dominant discourse of internationalization in East Asia, the dissenting voices expressed a mismatch between students’ understanding of internationalization and that embraced by the policy direction of the focal university. Students’ views expressed new insights into some long-standing issues of internationalization in non-Western societies, which are crucial for HE researchers and policy-makers in re-thinking the fundamental purposes and ultimate goals of contemporary higher education harnessed by the leading force of internationalization.